Investors Perception Towards Smart-Phone App Based Investments: An Investigation in Indian Context Exploring Relationship Between Trust and Usage Attitude. - Khatri, Arun (The journal of contemporary issues in business and government, 2022)
The tsunami of 4G technology and the evolution of revolutionary 5G on the horizon has changed the way people use their mobile-phones. The high speed and availability of internet to the common person has led the companies compete to find their place on the users‟ mobile phone screens. The trust of the consumers seems to be a pivotal factor when it comes to making financial investments online using smart-phones applications. More than fifty financial companies are providing the services of financial investments including mutual funds, IPOs, secondary share market, life insurance, general insurance, debt instruments, corporate and bank deposits, recurring deposits, bank services, central gold schemes, etc. The focus of theresearch study is to observe the impact of trust as a factor in the usage attitude of investors for app based investments. This primary research was carried out among the young and earning, mostly are regular users of mobile phone apps as an faster alternative to financial investments. A total of 250 questionnaires were distributed for the study and random sampling technique was used in the study. Thisstudy confirms that trust plays an important role and have a positive relationship with the attitude when it comes to financial investments. The conceptual framework adopted from Keng and Ting model (2009), establishing relationship of aesthetic; playfulness; service excellence and consumer return-on-investment (CROI) to usage-attitude. This study adopts the established-model by „Christine Ennew‟ and „Harjit Singh Sekhon‟ (2007) „Measuring trust in financial services: the trust index‟.